Allah Sang Pengatur Rumah Tangga - Senopati Salomo Olimbovo; Grant Nixon (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
As modern people, Christians often come to the book of Genesis, especially regarding the events of creation, with a scientific lens to seek answers to objections such as creation ex nihilo, regarding the age of the earth, as well as material things. John H. Walton proposed reading the creation story through a functional lens (creating order) rather than a material one. The researcher was then interested in seeing God as the ruler of the household through Walton's thoughts regarding women, especially housewives who are often seen as inferior to men who work or produce something. This paper uses a qualitative approach with data collection methods in the form of literature studies, especially regarding Walton's thoughts. The results of this research show that even on the first page of the book of Genesis, God has introduced himself as the God who brings order, the God who provides functions, and the God who regulates households which is also resonant with the function of housewives who are often discriminated against.